To find the product of the two given matrices, we need to perform matrix multiplication. Let's denote the first matrix as \( A \) and the second matrix as \( B \):
\[ A = \begin{pmatrix} 4 & 0 \ 0 & 3 \end{pmatrix}, \quad B = \begin{pmatrix} -1 & -2 \ -1 & 1 \end{pmatrix} \]
The product of two matrices \( A \) and \( B \) (resulting in matrix \( C = AB \)) is calculated by taking the dot product of rows of \( A \) with columns of \( B \).
The resulting matrix \( C \) will have the following entries:
- \( C_{11} \): First row of \( A \) dot with first column of \( B \)
- \( C_{12} \): First row of \( A \) dot with second column of \( B \)
- \( C_{21} \): Second row of \( A \) dot with first column of \( B \)
- \( C_{22} \): Second row of \( A \) dot with second column of \( B \)
Now we will compute each entry:
- \( C_{11} = 4 \cdot (-1) + 0 \cdot (-1) = -4 + 0 = -4 \)
- \( C_{12} = 4 \cdot (-2) + 0 \cdot 1 = -8 + 0 = -8 \)
- \( C_{21} = 0 \cdot (-1) + 3 \cdot (-1) = 0 - 3 = -3 \)
- \( C_{22} = 0 \cdot (-2) + 3 \cdot 1 = 0 + 3 = 3 \)
Putting it all together, we find that:
\[ C = AB = \begin{pmatrix} -4 & -8 \ -3 & 3 \end{pmatrix} \]
Thus, the product of the two matrices is:
\[ \begin{pmatrix} -4 & -8 \ -3 & 3 \end{pmatrix} \]